Spontaneously resolved invasive conjunctival squamous cell carcinoma with anterior chamber invasion in low-grade lymphoma patient - Tanya Boghosian; Promporn Patarajierapun; Ben J. Glasgow; Carla B. Berkowitz; Clemence Bonnet; Tara A. McCannel; Brad D. Barrows; Simon S.M. Fung (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of invasive conjunctival squamous cell carcinoma (SCC) with anterior chamber invasion that resolved spontaneously after incisional biopsy and anterior chamber paracentesis in the absence of any treatment. Observations: A 76-year-old man presented with a 3-month history of a recurrent mass in the right eye. Examination showed an elevated, smooth amorphous lesion at the nasal conjunctivae, adherent to the scleral surface. There was also a pseudohypopyon at the angle adjacent to the lesion. Incisional biopsy of the right conjunctival lesion and intracameral fine-needle aspiration (FNA) were performed, which confirmed recurrent invasive SCC. Brachytherapy was planned but was deferred when spontaneous regression of the lesion was noted at the interim visit. The lesion completely resolved within one year post-biopsy with no additional interventions and has remained with no signs of recurrence two years after regression, permitting uneventful cataract surgery for visual rehabilitation. Conclusions and Importance: Invasive conjunctival squamous cell carcinoma is an advanced form of ocular surface neoplasia, typically necessitating extensive surgical excision and chemical or biologic therapy. This case highlights a potential pathway for the spontaneous resolution of squamous cell carcinoma post-incisional biopsy, although the precise underlying mechanisms remain unclear. Understanding these mechanisms could inform future treatment for squamous cell carcinoma and other neoplasms.